EDIBLE FILM BASED ON ENZYMATICALLY PRODUCED NANOCELLULOSE: CHARACTERIZATION AND NOVEL USE IN PACKAGING BEEF CUTS - Alzobaidy, Hyder; Alquraishi, Muhsin (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
ABSTRACT Sustainable food packaging solutions with biocompatible macromolecules are becoming increasingly popular. This study addresses the difficulty of extending the shelf life of meat through innovative packaging. It investigates nanocellulose coatings as a possible solution for microbial growth and oxidative stability issues. The goal of this study is to develop a novel nanocellulose (NC) edible film to protect and extend the shelf life of meat cuts. In this study, cellulase is used in a modified method to convert microcrystalline cellulose (MCC) into nanoscales. X-ray diffraction analysis of enzymatically treated MCC revealed a decrease in crystallinity from 53.8% to 42.8%. Atomic force microscopy (AFM) images of cellulose fibers treated with cellulase show particles in the nano-dimensions, and the surface roughness profile has Rq and Ra values of 0.082 µm and 0.068 µm, respectively. Field-emission scanning electron microscopy (FESEM) images revealed that NC films have uniform nanoparticle distribution, and the nanoparticles range in size from 35 to 46 nm. The microbial content and chemical properties of the NC coating solution were studied in three treatments (T1, T2, and T3) with a control. The study examined the effects of NC coating on the microbial growth of aerobic bacteria, coliform bacteria, Clostridium bacteria, yeast, and mold. The control group showed significant growth in all microbial populations over the 10-day period. The treatment groups exhibited growth at lower levels compared to the control group. Meat with NC coatings has a significantly lower pH than control group meat, and NC coatings at higher concentrations improve oxidative stability and reduce lipid oxidation. NC coatings in meat cuts act as antioxidants, boosting oxidative stability, decreasing PV, and lowering lipid oxidation. As a result, this study introduced an innovative NC edible film to preserve meat cuts